From Dusk till Dawn: The Transformation and Conversion of the Pietist Missionary Treatise Or le-'et 'erev (The Light at Evening Time) and Its Dutch Translator. - Siluk, Avraham (Avi) (Jewish Quarterly Review)
Or le-'et 'erev was the most popular missionary pamphlet printed by the Pietist Institutum Judaicum et Muhammedicum in Halle (Saale). This Yiddish booklet garnered much attention among Jews and Christians alike, and it was translated into several languages, including Dutch. One Dutch translation was penned by a Jewish convert who later reverted to Judaism and faced various accusations relating to his translation. This article focuses on that Dutch translation and the largely unknown personality of its author. The translation and its accompanying paratexts are compared with another eighteenth-century Dutch translation of the same pamphlet, thus shedding light on the translation techniques used, as well as the nature of the work and its intended audience. The translator's multiple identities appear in a diverse corpus of documents under several aliases. In his largely unknown Hebrew apologia, Or le-'et boker , which demonstrates a profound knowledge of Judaism as well as remarkable literary skills, he rewrote the story of his reconversion as a tale of repentance and redemption. Despite the idiosyncrasy of this fascinating life story, which transitions between Christianity and Judaism, the translator should be viewed as belonging to a larger group of less-known eighteenth-century Jewish authors and reformers. The members of this group sought to improve piety and religious education among their coreligionists and shared eighteenth-century Christian pietist notions of religiosity.